Miscellaneous topics in finite geometry: in memory of Professor Dr. Ferenc Kárteszi (1907-1989) - Zeitler, Herbert (Teaching Mathematics and Computer Science, 2006)
The article starts with a short introduction to finite (K,L)-geometry. Then a lot of counting propositions is given and proved. Finally the famous theorem of Miquel is investigated in classical and in finite geometry. At the end of the article there is a call to all readers: Don't forget (finite) geometry and don't forget the outstanding geometer Prof. Dr. F. Kárteszi!